The Poison at the Source - Brown, P. author. aut Link
IX, 259 p.
Keywords: An examination of a number of English women novelists who portrayed the crises and conflicts in the development of the female consciousness as a response to the anomalies of the rapidly changing world of the early twentieth century when opportunities for self-expression and fulfilment were beginning to open up for women but nineteenth-century values and prejudices still widely prevailed. May Sinclair, Radclyffe Hall, Rosamond Lehmann, Antonia White and Dorothy Richardson are seen as outspoken and innovative writers often marginalised or ignored by serious criticism.